Duodenal Fistula. Drainage Complication of Hepatic Hydatid Cavity - Laviña, Raúl E; Perrone, Luis; Pamparato, Mario; Venturino, Walter (Cirugía del Uruguay, 1980)
Repcrt of the case of a patient carrying hepatic hydatid. echinococcosis. Surgery involved evacuation and external drainage, However, during distant postoperatory evolution there developed a duodenal fistula along the path of drainage tube. The case is discussed.